Governança ambiental na Reserva de Desenvolvimento Sustentável Igapó Açu (Amazonas, Brasil) - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The miriad of social actors involved in the process of creating and implementing a Conservation Unit has emphasized the importance of the debate on environmental governance in these units. In this sense, the main objective of this research was to analyze the environmental governance in the Sustainable Development Reserve Igapó Açu, located in the municipalities Manicoré, Borba and Beruri. The choice of the study area is due to the fact that the RDS Igapó Açu be the only UC Amazonas crossed by a federal highway, which gives it a specific land use planning and reconfigures the elements of governance in that territory. To achieve the main objective of the research, above earlier, were three specific objectives set: to demonstrate the network of relationships between the actors involved in the governance of UC, understand existing forms of social organizations and its consequences on governance; and describe the weaknesses and strengths of territory management resulting from the governance of RDS Igapó Açu. To achieve these objectives we used different methodological tools such as forms, open interviews, participants workshops, SWOT Matrix, and Websphere Analysis Program. The survey results indicate that the fabric of environmental governance RDS Igapó Açu involves multiple factors, however, the centrality of political articulation network is occupied by the Management Board, leading to the materialization of the governance of UC and its consequences. Forms of social organization emerge and configure the network policy articulation and influence in regional planning from the power relations that are intrinsic. The management of the territory, the modus operandi of governance, materializes in a participatory manner, in that the processes of creation of UC and decision-making involved and involve all the social actors of the territory. In this sense, it sets up a democratic governance, where the Management Board provides the necessary conditions for the development of governance, and the head of the UC the essential conditions for the implementation of management. Therefore, the results of this research indicate, in general, that environmental governance RDS Igapó Açu is established through the interaction of symbolic systems and socio-political systems, leaders of the forms of social organization. The territoriality that UC, coming from the interactive process part listed above, is aligned to a specific way of life, based on social practices that ensure and perpetuate environmental sustainability. It can therefore be concluded that the democratic environmental governance RDS Igapó Açu has been successful, in that it has ensured the goals and objectives set forth in the Management Plan. Barriers exist because of the multitude of interests and stakeholders involved in the political articulation of the network, but the results show that progress has been significant.
Keywords: Rede Política; Sustentabilidade; Governança Ambiental; CIÊNCIAS AGRÁRIAS: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL